Education Basics Of Financial Planning Prospective Intern Japan - Aji Erlangga; Novfitri Landong Namora Sihombing Novfitri Sihombing; Amrizal Amrizal; Henny Mulyati (Yayasan Ilomata, 2020)
Japanese technical apprenticeship opportunities for developing countries, including Indonesia. The program is called with the Technical Internship Training Program officially run by the respective governments. Apprentices from Indonesia had the opportunity to undergo an internship program for three years and earn wages while in Japan. Delivery interns from Indonesia, operationally performed by LPK (Employment Training Institute), who get permits and supervised by the Ministry of Manpower. Preparations made by the CAB include language training and technical skills, but not include things beyond the core financial management program. With the chance to get a monthly income that is worth 3-4 times more than the minimum wage in Indonesia, but only lasted three years (36 months), then the knowledge of the purpose and financial planning becomes essential. Activities by the Indian Institute of Technology and Business Ahmad Dahlan fill the void giver material in the aspect of financial literacy.